Kemampuan siswa SMP di eks Karesidenan Kediri dalam menyelesaikan soal-soal matematika model TIMSS - Sari, Dwi Cahya; Jailani, Jailani (Jurnal Pendidikan Matematika dan Sains, 2018)
Penelitian ini bertujuan untuk mendeskripsikan kemampuan siswa SMP kelas VIII di eks Karesidenan Kediri dalam menyelesaikan soal matematika model TIMSS. Teknik pengambilan sampel menggunakan teknik sampling strata. Sampel penelitian sebanyak 465 siswa yang berasal dari sekolah strata tinggi, sedang dan rendah berdasarkan nilai ujian nasional matematika. Pengumpulan data menggunakan tes dengan instrumen soal matematika model TIMSS. Hasil penelitian menunjukkan bahwa kemampuan siswa dalam menyelesaikan soal matematika model TIMSS pada sekolah strata tinggi termasuk kategori tinggi, pada sekolah strata sedang dan rendah termasuk kategori sedang. Ditinjau dari domain konten bilangan, pada sekolah strata tinggi dan sedang termasuk kategori tinggi, pada sekolah strata rendah termasuk kategori sedang. Domain aljabar pada sekolah strata tinggi dan sedang termasuk kategori sedang, pada sekolah strata rendah termasuk kategori rendah. Domain geometri pada sekolah strata tinggi termasuk kategori tinggi, pada sekolah strata sedang dan rendah termasuk kategori sedang. Domain data dan peluang pada sekolah strata tinggi dan sedang termasuk kategori tinggi, pada sekolah strata rendah termasuk kategori sedang. Ditinjau dari domain kognitif pengetahuan pada sekolah strata tinggi dan sedang termasuk kategori tinggi, pada sekolah strata rendah termasuk kategori sedang. Domain penerapan pada sekolah strata tinggi termasuk kategori tinggi, pada sekolah strata sedang dan rendah termasuk kategori sedang. Domain penalaran pada sekolah strata tinggi termasuk kategori sedang, pada sekolah strata sedang dan rendah termasuk kategori rendah. The ability of junior high school students at ex Kediri Residency to solve the mathematic problems of TIMSS models Abstract This research is aimed to describe the ability of 8th grade junior high school student at Ex-Kediri Residency to solve the mathematic problems of TIMSS models. The sampling was stratified random sampling. Number of sample are 465 students. Samples were some students of 8th grade at Ex-Kediri Residency. These school include high, average, and low category based on the score in national examination of mathematics subject. The data collection was by tests. The research results showed that the ability of junior high school student at high stratum schools belongs to high category, at medium and low stratum schools belongs to average category. Judging from the numbers domain, at high and medium stratum schools belongs to high category, at low stratum schools belongs to average category. For algebra domain, at high and medium stratum schools belongs to average category,at low stratum schools belongs to low category. For geometry domain, at high stratum schools belongs to high category, at medium and low stratum schools belongs to average category. For data and chance domain, at high and medium stratum schools belongs to high category, at low stratum schools belongs to average category. Judging from the cognitive knowing domain, at high and medium stratum schools belongs to high category, at low stratum schools belongs to average category. For applying domain at high stratum schools belongs to high category, at medium and low stratum schools belongs to average category. for reasoning domain at high stratum schools belongs to average category, at medium and low stratum schools belongs to low category.